Exploring the guiding principles of collaborative acts in team sports - Uchiyama, H. (International Journal of Sport & Health Science, 2022)
The purpose of this study was to clarify guidelines for cooperation within an entity known as a "team" that transcend the individual, based on the theory that universal validity criteria and norms that are inherent in them play an important role in team victory. For this purpose, procedures were taken to outline team values and then formulate guidelines that are universally valid by extracting value criteria and normative principles from the analysis. The study results were as follows. 1) It was suggested that criteria allowing distinction between acceptable and nonacceptable actions performed by the team are essential for collaboration among individual athletes, and that conversely, a convergence of various values occurs among athletes. 2) The success or failure of collaborative acts should be based on 2 criteria: "whether or not team performance can be improved," and "whether or not individual athletes can be satisfied." In addition, it was clarified that teams and individuals acted in a binary manner, allowing the team to inspire individual athletes, while at the same time individual athletes inspired the team. 3) Finally, it was concluded that team victory is supported and ordered by 2 criteria with a normative principle that "personal assets accumulated through standard value judgments of `whether or not personal talents are utilized` do not reside with the individual as a right of nonaggression, but must be used for the team as a whole in accordance with its needs." It is anticipated that the present findings will not only help to solve practical problems in team sports, but will also contribute to the debate over athletic capability, which plays an important role in establishing team performance.